ANALISIS KINERJA SIMPANG DI JALAN H.M NOERDIN PANDJI - Gamara, M. Rizky Rewa; Rosyad, Farlin; Syarifudin, Achmad; Mulyati, ely (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Jalan Baru Intersection on Jalan H.M. Noerdin Pandji, Palembang, is a signalized intersection connecting strategic areas such as shopping centers, residential zones, and access to Sultan Mahmud Badaruddin II Airport. High traffic volumes during peak hours often cause congestion, making it necessary to analyze the intersection’s performance. This study aims to assess the existing conditions and evaluate the intersection’s performance through an intersection inventory survey, classified turning movement count, and cycle time survey, supported by secondary data from relevant agencies. Analysis was conducted using peak hour traffic volume data (07:00–08:00 WIB) totaling 10,412 vehicles/hour. Results show the highest traffic volume on Jalan Pangeran Ayin at 3,662 pcu/hour and the lowest on Jalan Sako Baru at 1,375 pcu/hour. The average queue length reached 83.41 meters, with the longest queue at 120 meters. The average delay was 56.9 seconds/pcu, categorized as LOS E, indicating near-saturated flow with moderate to high delays. Overall, the intersection can still accommodate peak hour traffic, but performance is declining on certain approaches, particularly Jalan Pangeran Ayin and Jalan Sako Baru.Keywords: Intersection Performance, Traffic, LOS, Congestion, Palembang